PAUD TEACHER PERFORMANCE THROUGH ACADEMIC SUPERVISION IN PLAYGROUPS (KB) IN ACEH TAMIANG REGENCY - Fitrie Rahmawaty; Hera Yanti; Siraj (World Psychology, 2025)
A phenomenon observed among several Early Childhood Education (PAUD) teachers in Aceh Tamiang Regency indicates that service performance in playgroups (KB) is relatively low. This low performance is evidenced by a lack of understanding regarding play-based learning, weak proficiency in developing Daily Lesson Plans (RPPH), and minimal innovation in the use of instructional media. This study aims to examine the implementation of academic supervision—encompassing the stages of planning, implementation, and follow-up—designed and implemented to enhance the performance of playgroup teachers in Aceh Tamiang Regency. This research offers a new perspective on how reflective and collaborative supervision structures can serve as a capacity-building mechanism for PAUD teachers at the local level. A qualitative descriptive approach was employed. Data collection techniques included interviews, observations, and documentation. The research subjects consisted of school principals, teachers, and school committee members. The findings indicate that the academic supervision process has incorporated elements of planning, implementation, and follow-up, although its application is not yet fully systematic. During the planning stage, the coaching focus was directed toward improving teachers' abilities in drafting RPPH, developing learning strategies, and conducting child development assessments. Supervision was carried out through classroom observations and reflective dialogues, while follow-up actions were realized through joint reflection and corrective guidance. However, the sustainability of monitoring and coaching activities still requires stronger policy frameworks and institutional support. This study asserts that structured and sustainable academic supervision is determined not only by procedures but also by the positive contribution toward increasing the willingness and capability of both supervisors and teachers in fulfilling their professional duties.